Valuasi Ekologis terhadap Alih Fungsi Lahan Sawah di Kabupaten Bandung, Jawa Barat - Achmad, Mubarik; Labida, Lulu; Djuarsa, Febby Firdian; Ernah, Ernah (Universitas Galuh, 2025)
The conversion of rice fields into non-agricultural areas in Bandung Regency has continued to rise in line with rapid urbanization and infrastructure development. This phenomenon not only reduces agricultural land area but also leads to the loss of essential ecosystem services such as food production, water conservation, and carbon sequestration. This study aims to assess the ecological value of converted rice fields through a review of national and international literature and a local case study. This research applies a quantitative descriptive method using a case study approach in Bandung Regency. The valuation technique uses the Market Price Method (MPM) to estimate the economic value of lost food production services due to land conversion. Secondary data were obtained from BPS, the Agricultural Office, and previous studies, and analyzed through ecosystem economic valuation based on market prices and land use changes. The findings indicate that between 2019 and 2024, approximately 2,413 hectares of rice fields were converted. Assuming a rice yield of 5.6 tons/hectare/season, two planting seasons per year, and a dry grain price of Rp7,800/kg, the estimated economic loss in food production services reaches Rp210.8 billion. These results highlight the importance of integrating ecological valuation into spatial planning and farmland protection policies. Recommendations include strengthening land protection regulations, providing ecosystem service-based economic incentives, and improving spatial monitoring systems to prevent unsustainable land conversion.